The Optimal Team Functioning Model: A Grounded Theory Framework to Guide Teamwork in Curling. Issue 4 (2nd October 2019) - Collins, Jamie; Durand-Bush, Natalie
Abstract : A constructivist grounded theory approach was used to investigate teamwork and team effectiveness in the sport of curling. Focus group and individual interviews were conducted with 78 athletes and 10 coaches from 19 high-performance curling teams. Data analysis led to the creation of the Optimal Team Functioning (OTF) model, which comprises 8 key components for optimal team functioning: (a) individual attributes, (b) team attributes, (c) foundational process of communication, (d) structural team processes, (e) individual regulation processes, (f) team regulation processes, (g) context, and (h) desired outcomes. Components and relationships within the model, along with practical implications, are discussed. Lay Summary : Developing effective sport teams is a challenging and complex process. Unfortunately, few resources are available to guide coaches and athletes in their efforts to optimally function and perform as a unit on a daily basis. This novel team dynamics research was carried out with high-performance coaches and athletes to uncover a comprehensive and ecologically valid model mapping out effective teamwork within the sport of curling. The Optimal Team Functioning Model focuses on concrete actions that can be applied to successfully set up and manage a team and its individual members throughout a season.